Penentuan Cadangan Premi Prospektif Untuk Asuransi Pendidikan Di PT Bhinneka Life Regional Padang - Sari, Utri Mayang; yurniati, Yurniati; Resti S, Siska (Program Studi Aktuaria, Fakultas Sains Teknologi dan Pendidikan, Universitas Tamansiswa Padang, 2024)
The purpose of this study is to obtain a formula for calculating the premium reserve value prospectively calculating education insurance. The case study in this study examines the value of premium reserves at the age of 26-30 years with a coverage period of 16-17 years with an interest rate of 3.50%. In determining the value of premium reserves using prospective calculations. This will begin by completing the 2019 Indonesian Mortality Table values ??using an interest rate of 3.50%, calculating the value of a term life annuity, single net premium for endowment/endowment life insurance, annual premium value for education insurance. The results of this study indicate that the premium reserve value with prospective calculation of the benefits embedded at the end of the year and the value of the premium reserve for benefits imposed when the insured dies, painting with the value of the cash price set by the insurer at the end of the 17th year on the insurance contract .